FACTORS INFLUENCING CUSTOMER DECISIONS IN CHOOSING HOUSING LOANS (KPR) AT BTN SYARIAH KCPS MEULABOH - Purnama Sari, Siska (International Asia Of Law and Money Laundering (IAML), 2024)
This study aims to analyze the factors influencing customer decisions in choosing Sharia Home Ownership Loans (KPR) at BTN Syariah KCPS Meulaboh, West Aceh. Using a quantitative approach and descriptive analysis method, this research involved 100 respondents selected through purposive sampling. Data was collected through structured questionnaires and analyzed using multiple linear regression with SPSS version 23.00. The results indicate that competitive margins and efficient application procedures have a positive effect on customer decisions. However, payment flexibility has a negative impact. Classical assumption tests show that residuals are normally distributed according to the Kolmogorov-Smirnov test, there is no multicollinearity, but there is an indication of potential heteroscedasticity in the payment flexibility variable. The resulting regression model can explain about 39.0% of the variability in customer decisions. This study provides valuable insights for BTN Syariah KCPS Meulaboh to improve their Sharia KPR services and products, focusing on competitive margins, streamlined application procedures, and a better understanding of customer preferences regarding payment flexibility.